Behavior Support Strategies in Singapore Preschools: Practices and Outcomes. (October 2019) - Lau, Lily H. S.; Moore, Dennis W.; Anderson, Angelika
This study evaluated teachers' use of universal Program-Wide Positive Behavior Support (PW-PBS) practices at a class-wide level, the rate of disruptive behavior, and the level of academic engagement in Singapore preschool general education classrooms. Evaluation was carried out in 32 classrooms using mainly direct observational methods. Findings indicated that while the majority of the teachers taught rules and expectations to children several times throughout the year, used effective error corrections, and allocated more than 70% of class time to academic instructions, none of them had a system for documenting and rewarding appropriate child behavior, or a documented system to address specific behavioral violations. Very few teachers used a continuum of consequences to manage rule violations, and the use of general and behavior-specific praise was low. Furthermore, rates of disruptive behavior were relatively high, which were associated with high rates of reprimands, and one third of the classrooms had low academic engagement levels. Methods of enhancing teacher training in universal practices are discussed.